Childhood retinoblastoma - Ramyuzal Nasution; Adi Sutjipto (Paediatrica Indonesiana, 1991)
Childhood retinoblastoma was studied in a period of January 1980 to December 1988. Forty six patients were included consisting of 21 males (45.65%) and 25 females (54.35%). Most of those patients (76.08%) were in the age group of 0- 5 years. The main complaint was protrusion of eyes, found in 42 patients (91.30%). Bone marrow examination was done in 24 patients, and 52.17% of them showed sign of metastasis. Thirty seven cases had unilateral retinoblastoma (80.43%). The statistical analysis indicated no significant differences in sex and age, site of tumor (left or right eyl!l), abnormality of the eyes, bone marrow involvement, protrusion of the eyes either unilateral or bilateral. Heredity was found in one patient (2. 17%). The main treatment was radiation in 25 patients (50.43%).